Inhibition of platelet activation in congestive heart failure by aldosterone receptor antagonism and ACE inhibition - Schäfer, Andreas; Fraccarollo, Daniela; Hildemann, Steven; Christ, Michael; Eigenthaler, Martin; Kobsar, Anna; Walter, Ulrich; Bauersachs, Johann (Thrombosis and Haemostasis, 2003)
An increased risk of thrombembolic events in congestive heart failure (CHF) has been attributed to a hypercoagulable state including vascular endothelial dysfunction and platelet activation.After experimental myocardial infarction, male Wistar rats were treated with placebo, the ACE inhibitor trandolapril, the selective aldosterone receptor antagonist eplerenone or the combination of both, for 10 weeks. Platelet-bound fibrinogen and surface-expressed P-selectin were not modulated in rats without CHF compared with sham-operated animals, but were significantly increased in CHF rats (LVEDP>15mmHg). In CHF rats, ACE inhibition significantly reduced platelet P-selectin expression while bound fibrinogen was not modulated. Eplerenone reduced P-selectin expression to a comparable extent, while platelet-bound fibrinogen was normalised. Combination therapy with eplerenone and trandolapril completely abolished both the increased P-selectin expression as well as fibrinogen binding. Phosphorylation of platelet vasodila-tor-stimulated phosphoprotein (VASP) at both Ser157 and Ser239, which reflects the activity of platelet inhibitors including nitric oxide, was significantly reduced in platelets from placebo-treated CHF rats, and was completely normalised by combination treatment, but only marginally increased by either mono-therapy.The results show that platelet activation was evident only in CHF rats. Monotherapy with ACE inhibition or eplerenone partially reduced this increased platelet activation, which was completely rescued to basal levels by combination therapy. Increased nitric oxide bioavailability can only partially explain the reduced platelet activation by eplerenone and ACE inhibition.
Keywords: Heart failure; platelets; infarction; aldosterone; nitric oxide